‘URF AS AN EPISTEMOLOGICAL FRAMEWORK FOR VALIDATING LIVING LAW: A CRITICAL READING OF ARTICLE 2 OF INDONESIA'S 2023 CRIMINAL CODE - Adi Harmanto; Asasriwarni; Ikhwan; Juliani Syafitri (JAS : Jurnal Ahwal Syakhshiyyah, 2026)
Article 2 of Law No. 1 of 2023 on the Criminal Code recognizes “living law” as a basis for criminal punishment but does not provide adequate criteria to distinguish customary norms that deserve penal force from those that risk reproducing injustice. The core problem is epistemic incompleteness in validating customary norms, which risks institutionalizing injustice, as reflected in discriminatory local policies and gender‑asymmetric customary sanctions. This normative legal study employs a comparative‑epistemological approach, operationalizing the doctrine of ‘urf in uṣūl al‑fiqh as its analytical framework. Three main findings emerge. First, the epistemology of ‘urf offers a structured mechanism for validating norms through the ‘urf ṣaḥīḥ–‘urf fāsid distinction and its corrective function. Second, reading Article 2 through this lens reveals three structural alignments and five epistemological tensions, with the absence of a corrective function as the most fundamental weakness. Third, four verification standards social, substantive, temporal, and authoritative are formulated as an operational framework for the derivative regulations mandated by Article 2(3). The article thus positions Islamic law as an epistemological partner that transcends the formalization marginalization dichotomy and frames decolonization of criminal law as an epistemological transformation of the sources, limits, and legitimacy of punishment. Keywords: 'urf epistemology; living law; criminal code; legal pluralism; corrective function